RESPON PERTUMBUHAN BIBIT CENGKEH (Syzgium aromaticum (L.) Merr dan Perry) KULTIVAR ZANZIBAR AKIBAT PUPUK NPK DAN PUPUK ORGANIK CAIR - Yudi Yusdian; Ridwan Haris (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2016)
The objective of this research was to study the response on the growth of clove seedling cultivar Zanzibar as the result of using NPK Phonska fertilizer dosage and liquid organic fertilizer concentration and to find out the acurate dosage of NPK Phonska and liquid organic fertilizer “Getoe”. The experiment was conducted at Kampung Ciherang Desa Gunungtua Kecamatan Cijambe Kabupaten Subang, West Java. The altitude is about 600 m above sea level, the soil type is Ultisol (pH 5,4), the average of rainfall was 1622,10 mm/year and the type of rainfall is C according to Schmidt and Ferrguson (1951). The experiment from March 2014 until June 2014. The experiment was arranged in Randomized Block Design (RBD) consisted of six treatments, i.e : A (2,5 g NPK + 0 cc/L of water POC Getoe), B (1,5 g NPK + 2,5 cc/L of water POC Getoe), C (2,0 g NPK + 2 cc/L of water POC Getoe), D (2,5 g NPK + 1,5 cc/L of water POC Getoe), E (3,0 g NPK + 1,0 cc/L of water POC Getoe) and F (3,5 g NPK + 0,5 cc/L of water POC Getoe) and replicated six times respectively. The result of this research showed that combined 2,5 g NPK fertilizer and 1,5 cc Getoe liquid organic fertilizer concentration gave the better effect on stem height, leaves of number, leaf area, dry weight of plant and dry weight of root the clove seedling cultivar Zanzibar.